UFUR maintenance therapy significantly improves survival in locally advanced head and neck squamous cell carcinoma following definitive chemoradiotherapy - Jason Chia-Hsun Hsieh; Ming-Yu Lien; Pei-Hung Chang; Hung-Ming Wang; Kun-Yun Yeh; Ching-Liang Ho; Ching-Yun Hsieh; Meng-Che Hsieh; Jia-Hong Chen (Cancer Cell International)
Abstract Background Head and neck squamous cell carcinoma (HNSCC) presents significant therapeutic challenges, particularly in patients with advanced disease. Despite advancements in treatment, high recurrence rates and poor overall survival (OS) remain major concerns. This study evaluates the impact of tegafur-uracil (UFUR) maintenance therapy on survival outcomes in patients with advanced HNSCC following definitive chemoradiotherapy. Methods A cohort of 424 advanced HNSCC patients treated with definitive chemoradiotherapy were analyzed, with a median follow-up of 25 months. Patients were stratified into UFUR (+) and UFUR (-) groups, with baseline characteristics balanced across both arms. Oncologic outcomes, including recurrence-free survival (RFS), OS, locoregional recurrence-free survival (LRFS), and distant metastasis-free survival (DMFS) were compared between these groups. Results UFUR maintenance therapy significantly reduced recurrence rates (34% vs. 47%, p < 0.002), driven primarily by improving locoregional control (23% vs. 37%, p < 0.001). While distant metastasis rates were similar between groups, UFUR (+) patients demonstrated a markedly improved median OS (51.6 months vs. 24.3 months, p < 0.001). The UFUR (+) group also showed superior median LRFS (36.9 months vs. 20.2 months, p = 0.003) and DMFS (44.0 months vs. 23.5 months, p = 0.010). Subgroup analysis confirmed the benefits of UFUR maintenance across different stages of disease. Multivariate analysis identified UFUR maintenance, gender, and T stage as independent predictors of survival. Conclusion UFUR maintenance therapy significantly improves survival outcomes in patients with advanced HNSCC following definitive chemoradiotherapy, particularly through enhanced locoregional control, and should be considered a key component of personalized treatment strategies.